BIPV-temp: A demonstrative Building Integrated Photovoltaic installation. (1st July 2016) - Chatzipanagi, Anatoli; Frontini, Francesco; Virtuani, Alessandro
Highlights: Monitoring of a demonstrative Building Integrated Photovoltaic (BIPV) installation. Modules at/of different: inclinations, integration solutions and technologies. Investigation of performance and working temperatures of the modules. NOCT and ECT models were used for the calculation of the junctions' temperatures. Abstract: This paper presents the results of a demonstrative Building Integrated Photovoltaic (BIPV) installation in Lugano where five BiPV modules with different integration solutions (fully integrated as Double Glaze Units (DGUs) and ventilated), different inclinations (30° and 90°) and different technologies (double junction amorphous silicon (a-Si/a-Si) and crystalline silicon (c-Si)) were investigated. The paper aims at evaluating the impact of the operating cell temperature on the modules' performance for different investigating cases. Two models were used to calculate the junctions' temperatures of the modules under operation: the simplified Nominal Operating Temperature (NOCT) model and the Equivalent Cell Temperature (ECT). The first was used in a simplified version and the second was used for all modules, regardless of its limitations for thin film technologies. The two models agree well and give satisfactory results regardless of the inclination, integration solution or technology. The difference between the NOCT and ECT calculated average daily temperatures of the modules was found to be less than 5–6 °C, with only one exception. As expected, fully integrated modules exhibit higher temperatures. In terms of performance, the integrated c-Si modules, regardless of their inclination, ranked lower – in terms of energy yield – than the integrated and ventilated a-Si/a-Si modules, for which the high operating temperatures proved to be beneficial. The inclination of 90° was found to be ideal for Lugano for both c-Si and a-Si/a-Si modules.